Chinese Medicines and Natural Medicine as Immunotherapeutic Agents for Gastric Cancer: Recent Advances - Zhipeng Zhang; Ziqi Chen; Zujun Que; Zhihong Fang; Huirong Zhu; Jianhui Tian (Cancer Reports, 2024)
ABSTRACT Backgroud According to the 2020 statistics from the World Health Organization’s International Agency for Research on Cancer (IARC), it is projected that there will be over 1 million new cases of gastric cancer (GC) patients worldwide in 2020, resulting in approximately 770 000 deaths. Gastric cancer ranks fifth in terms of incidence rate and forth in death rate among malignant tumors. Despite advancements in early diagnostic techniques, the incidence of GC has exhibited a marginal decline; nevertheless, the mortality rate remains elevated for advanced inoperable patients with no currently available efficacious treatment options. Recent Finding Chinese medicine (CM) has emerged as an efficacious treatment for GC, gradually gaining acceptance and widespread usage in China. It exhibits distinctive advantages in the prevention and treatment of metastasis. CM and natural medicine possess the ability to elicit antitumor effects by augmenting immune cell population, enhancing immune cell activity, and improving the tumor immune microenvironment. CMs and natural remedies encompass a diverse range of types, characterized by multiple targets, pathways, and extensive pharmacological effects. Consequently, they have become a prominent research area among oncologists worldwide. Numerous studies have demonstrated that CM and natural medicine can directly or indirectly enhance innate immune system components (including macrophages, natural killer cells, and myeloid suppressor cells), adaptive immune system elements (such as T lymphocytes and regulatory T cells), relevant cytokines (e.g., IL‐2, IL‐4, IL‐10, TNF‐α), and PD‐1/PD‐L1 axis regulation, thereby bolstering the cytotoxicity of immune cells against tumor cells. Conclusions This ultimately leads to an improved tumor immune microenvironment facilitating superior antitumor efficacy. This paper critically examines the role of CM and natural medicine in regulating immunotherapy for GC, aiming to establish a new theoretical framework for the clinical treatment and prevention of gastric cancer within the realm of CM.